A.02 Clinical clues for autoimmunity in the etiology of autistic regression. (17th June 2016) - Goez, H; Scott, O; Shi, D; Andriashek, D; Clark, B
Abstract : Background: Autistic regression (AR) accounts for 20-40% of patients with Autism Spectrum Disorder (ASD) . 1 Literature demonstrates specific immune changes in AR patients, 2 as well as association between AR and autoimmune thyroiditis. 3 Our study explores the clinical association between AR and autoimmunity, focusing on possible precipitants and familial autoimmunity, in comparison with patients with infantile autism (IA).Methods: charts of children diagnosed with ASD in 2014 were reviewed, and patients were classified as either AR or IA based on Autism Diagnostic Interview (ADI-R) criteria. 4 Information regarding pregnancy, perinatal complications, febrile illness preceding the diagnosis, and family history of autoimmune conditions was collected.Results: 206 children had IA and 33 had AR. No difference was found in prevalence of pregnancy or perinatal complications. The incidence of febrile illness in the 6 months prior to diagnosis and the prevalence of familial autoimmunity, were significantly higher in the AR group (p<0.001). Diabetes type I, celiac disease, autoimmune thyroiditis, and inflammatory bowel disease were more common in families of AR patients (p<0.05).Conclusions: the association between AR and preceding febrile illness, as well as familial autoimmunity, supports the notion of AR as a separate entity within ASD, possibly mediated by autoimmune changes.